IMPLEMENTING COLLABORATIVE STRATEGIC READING TO IMPROVE STUDENTS’ READING COMPREHENSION - Azizah Batubara (English Language Teaching and Research, 2018)
As many students of SMAN 3 Padang Panjang have problems in comprehending English texts, some strategies, methods or techniques have been applied for years. In fact, Collaborative Strategic Reading has become one of the best practices among others. This strategy helps the students to guess the meaning of words/phrases/sentences based on context,  get the general idea, find explicit and implicit information, summarize the text, get the gist, cope with the questions which require the students’ higher order thinking and retell or summarize the  content of the text. Although the students needed to adapt with the strategy  at the first time they did it, they could finally achieve better reading comprehension as the writer analyzed the problems faced by the students and improved the implementation of this strategy for the next meeting. This  strategy helped most students to minimize the difficulties in guessing the meaning of words/phrases/sentences based on context,  getting the general idea, finding explicit and implicit informations, summarizing the text, getting the gist and coping with the questions which require the students’ higher order thinking skills as well as retelling or summarizing the content of the text. This best practice report is aimed at exposing and sharing the experience about how Collaborative Strategic Reading strategy was implemented and how this technique can help the students to improve and overcome the problems found  in reading comprehension classes of grade XII in 2018/2019 academic year.  Key words: Collaborative Strategic Reading,  improve, students’ reading comprehension